ANALYSIS OF SAK EMKM ANDROID-BASED APPLICATIONS' USE IN TANDES DISTRICT'S MSME FINANCIAL REPORT COMPILATION - Ardinesyah Hibatul Alim; Sri Trisnaningsih (International Journal of Economics, Business and Accounting Research (IJEBAR), 2023)
The goal of this study was to ascertain how the Application Information System Application for Financial Information Recording (SI APIK) was being used to compile financial reports for MSMEs in Tandes District in accordance with Micro, Small and Medium Entity Financial Accounting Standards (SAK EMKM). In this study, which takes a descriptive approach, qualitative research methodologies and approaches are used. In this study, observation, interviews, and documentation were used as data collection methods. In qualitative research, data analysis was done before going into the field, while in the field, and after returning from the field. The implementation of Android-based accounting applications can aid in the preparation of MSME financial reports, according to the study's findings. The output results are in line with SAK EMKM as well. MSMEs are capable of capturing anything, particularly commercial transactions. Because the SI APIK program currently employs a very user-friendly methodology. All transactional proof has been correctly archived in the SI APIK application's database. Additionally, you can view transaction history for the selected time frame.